Pond Farmers’ and Stakeholders’ Satisfaction in the Mangrove Planting Program in the Mahakam Delta, Indonesia - Boa, Handayani; Suwannathep, Sasitorn; Gunawan, Bambang I; Bunnag, Boosya (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
In order to encourage rural development and sustainable management of shrimp ponds in the Mahakam Delta area, the government and other organizations have initiated a mangrove planting program in green belts, inside ponds, and abandoned ponds as barren and inactive ponds that are degraded by pond extension through a mangrove planting program since 1999. It is indicated that the program's impact on the community in the Mahakam Delta could be realized when those local people participate more. The research involved 272 pond farmers and 33 stakeholders as the respondents. Analytical techniques for this study were descriptive statistics by applying the scoring on the Likert scale, and employing the chi-square test. The objectives of the study were (1) to measure pond farmers’ and stakeholders’ satisfaction with the mangrove planting program, (2) to analyze variables that correlate with pond farmers’ satisfaction with the mangrove planting program. The results showed that most pond farmers and stakeholders were well satisfied with the mangrove planting program in the Mahakam Delta. Pond farmers’ satisfaction was 7.7% in the highest score, 53.8% in the high score, and only 38.5% were at a low score. Also, 7.7%, 38.5%, and 38.5%, 15.4% of stakeholders’ satisfaction fell into highest, high, moderate, and low scores, respectively. In the analysis, three variables, which were the farming system adoption (Z1), education (Z2), and length of stay in the Mahakam Delta area (Z3) were associated with pond farmers’ satisfaction with the mangrove planting program. Therefore, the local people's satisfaction and characteristics can be considered in developing a strategy for the sustainability-enhancing of mangrove-shrimp farming management. Where, the government needs to realize the policies to mangrove trees planting within ponds, distance setting of green belt area, and improvement of skill and knowledge of local people.